Lower bounds on density for topologically nontrivial minimal cones up to dimension six - Jacob Bernstein; Lu Wang (Forum of Mathematics, Sigma)
We prove lower bounds on the density of regular minimal cones of dimension less than seven provided the complements of the cones are topologically nontrivial.